Yabancı yatırımcıların Türkiye’de karşılaştığı sorunlar - Pandul, Hüseyin Cihan (My University, 2005)
Doğrudan yabancı yatırım son yirmi yılda çokuluslu girişimler için ticaret işletmelerini bütün dünyaya, özellikle rekabete dayanan avantaja sahip olan bölgelere, yaymada başlıca vasıta olmuştur. Diğer yandan yabancı sermaye gelişmekte olan ülkelerin sermaye ve teknoloji seviyesine yaptıkları girdi ile ekonomik gelişmelerine katkıda bulunmuştur. Türkiye 1980'de ekonominin liberalizasyonundan sonra bile büyük miktarlarda doğrudan yabancı yatırımı çekmekte başarısız olmuştur. Bu araştırma doğrudan yabancı yatırımda ev sahibi ülkenin belirleyici ekonomik etkenlerini ele alarak Türkiye'deki iş çevresini incelemektedir. Türkiye'nin Avrupa Birliği'ne giriş süreci ve bunun dış yatırımlara olası etkisinin doğrudan yabancı yatırım akışını çekmede bir katalizör görevi üstlenmesi beklendiği için bu çalışmada irdelenmektedir. Birinci bölümde, betimsel strateji Türk iş çevresinin karakteristiklerini resmetmeyi amaçlamaktayken; incelemeci strateji çalışmanın ikinci bölümünde problemi açıklığa kavuşturmayı ve olguyu değerlendirmeyi amaçlar. Bunu takiben, vak'a çalışması projesi Türk otomotiv sektörünün son on yıldaki başarısını resmetmektedir. Çalışma politik ve ekonomik istikrarsızlık, yasal çerçevenin zayıflığı, yetersiz idare sistemi ve yozlaşmanın uygun bir yatırım ortamını sağlanmasını ve böylelikle büyük miktarlarda doğrudan yabancı yatırımı çekilmesini engelleyen ana problemler olduğunu belirtmektedir. Avrupa Birliği süreci Türkiye'ye düzenlemeleri dayatması ve böylelikle yatırım ortamına istikrar getiric olmasından ötürü yardımcı bir etmen olarak görülmektedir. GENERAL KNOWLADGE Name and Surname: Hüseyin Cihan PANDÜL Field: Business Programme: International Business Supervisor: Prof. Dr. Niyazi BERK Degree Awarded and Date: Master - July 2005 Key Words: Foreign Direct İnvestments, Turkish Business

Foreign direct investment has been the major vehicle for multinational enterprises in the last two decades to expand business operations all over the world particularly to the places that provide competitive advantages. On the other hand, foreign investment has contributed to economic development of emerging countries with its great input to their capital and technology level in the country. Turkey has been unsuccessful in attracting large amount of foreign direct investment even after the liberalization of economy in 1980. This research examines the business environment in Turkey and analyzes the main impediments, which lessen inwards, by applying the host country determinants of foreign direct investment. European Union process of Turkey and its possible impact on foreign investment is also evaluated since it is expected to be a catalyst in attracting foreign direct investment inflows. In the first part, descriptive strategy draws the characteristics of Turkish business environment whereas exploratory strategy aims to clarify the problem and assess the phenomena at the second part of the study. Following this, the case study design illustrates the success of Turkish automotive sector in the last decade. Research indicates that politic and economic instability, weakness of legal framework, insufficient administration system and corruption have been the main problems that prevent providing favorable investment climate, thus, attracting large amount of foreign direct investment. The European Union process is found to be a helpful factor to eliminate those problems by imposing regulations on Turkey, therefore stabilizing and enhancing the investment environment.
Keywords: Yabancı Sermaye